Mechanical and thermal transmission properties of carbon nanofiber‐dispersed carbon/phenolic multiscale composites. Issue 5 (22nd January 2013) - Bhattacharyya, Amitava; Rana, Sohel; Parveen, Shama; Fangueiro, Raul; Alagirusamy, Ramasamy; Joshi, Mangala
Abstract The present article reports the development and characterization of carbon nanofiber (CNF)‐incorporated carbon/phenolic multiscale composites. Vapor‐grown CNFs were dispersed homogeneously in to phenolic resin using an effective dispersion route, and carbon fabrics were subsequently impregnated with the CNF‐dispersed resin to develop carbon fiber/CNF/phenolic resin multiscale composites. Mechanical and thermal transmission properties of multiscale composites were characterized. Elastic modulus and thermal conductivity of neat carbon/phenolic and multiscale composites were predicted and compared with the experimental results. It was observed that incorporation of only 1.5 wt % CNF resulted in 10% improvement in Young's modulus, 12% increase in tensile strength, and 36% increase in thermal conductivity of carbon/phenolic composites. Fracture surface of composite samples revealed the formation of stronger fiber/matrix interface in case of multiscale composites than neat carbon/phenolic composites. Enhancement of above properties through CNF addition has been explained, and the difference between the predicted values and experimental results has been discussed. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013